Investigating the Impact of Land Use Change on Sediment Yield for Hydropower Reservoirs through GIS Application - Abdul Razad A.Z.; Samsudin S.H.; Setu A.; Abbas N.A.; Sidek L.M.; Basri H. (Institute of Physics Publishing, 2023)
Catchments; Land use; Remote sensing; Sediments; Soils; Catchment area; GIS application; Hydropower reservoirs; Lake sand reservoirs; Land-use change; Reservoir sedimentation; Sediment delivery ratio; Sediment yields; Geographic information systems